Comparative governance reform in Asia democracy, corruption, and government trust - Wescott, Clay; Phitthaya Bowonwatthana (Research in public policy analysis and management ;, 2008)
Asian countries are highly diverse in terms of their wealth, culture, and historical experience. Yet, in different ways, they are working hard to improve public sector governance in areas such as democratic accountability, openness, transparency, integrity, government trust, high performance standards and combating corruption. The chapters in this book analyze and compare the experiences of Asian countries in carrying out governance reforms. Some of the questions tackled in this title are: how common reform packages designed for developed countries are implemented in developing countries? What happens in the reform diffusion process? What are the obstacles to reform success? The diversity of the Asian region is well reflected in these chapters, covering a range of topics, theories, methodologies, and findings. The book will be of interest to both academics and practitioners researching and working with public policy in the region.